MDCT angiography in evaluation of pediatric hemangiomas and peripheral vascular malformations - Ghasi, Rohini Gupta; Narayan, Varun; Thukral, Brij Bhushan (International Journal of Research in Medical Sciences, 2018)
Background: To evaluate the role of MDCT angiography in peripheral hemangiomas and vascular malformations in pediatric patients. Methods: Total of 36 consecutive pediatric patients with clinically suspected peripheral hemangiomas and peripheral malformations were included in the study. MDCT angiography and doppler sonography was done for all patients. Final diagnosis was made by response to treatment and follow up. The statistical significance of various MDCT findings and post processing techniques was calculated. p value of <0.05 was considered significant. Results: Venous malformations were the most common. The MDCTA features which were significant in diagnosing venous malformations were phleboliths (p=0.039), peak enhancement in venous or delayed phase, absence of soft tissue mass, lacy tangle of vessels on maximum intensity projection and volume rendered images. Features significant in diagnosing arteriovenous malformations were tortuous arterial feeders, peak enhancement in arterial phase (0.0001), early draining vein (p=0.0001), venous phase wash out (p=0.0001), tense tangle of vessels on maximum intensity projection and volume rendered images (p=0.0003). Phleboliths (p=0.43) and venous or delayed phase peak enhancement (p=0.69) were overlapping features in congenital hemangiomas and venous malformations. Arterial phase enhancement (p=0.10) and early draining veins (p=0.39) were overlapping features in infantile proliferating hemangiomas and arteriovenous malformations. However, presence of soft tissue mass (p=0.0001) and lack of venous phase wash out (p=0.0003) were differentiating features for hemangiomas. Conclusions: MDCT angiography can be used as a highly accurate modality to diagnose hemangiomas and vascular malformations. It has an advantage over color Doppler in depicting entire extent of deep lesions.